2017
DOI: 10.1021/acs.jpcc.7b04848
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Fatigue Resistance of Photochromic 1,2-Diarylethenes

Abstract: Photochromic diarylethenes represent one of the most important classes of molecular switches, and their fatigue resistance is reported in several papers. Previous studies have demonstrated that the presence of perfluorocyclopentene and methyl in the 4-positions of dithienylethenes improve the switching resistance. However, general guidelines to correlate chemical structure to fatigue resistance have not been found yet. In this work, we provide a different thought in the description of the fatigue resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In addition to the commercial applications such as in sunglass lenses, photochromic molecules allow light to be used to reversibly control molecular properties for the development of light-controllable molecular tools, 3 controlling energy transfer 4 or self-assembly, 5 acting as receptors, 6 powering molecular machines, 7 for drug delivery, 8 or modifying material properties. 9 Dithienylethene, 10 spiropyran, 5 , 11 oxazine 12 and azobenzene 9a , 13 are classic photochromic molecules and examples exist in all of these groups where visible light can be used to drive the photoisomerisation. More recently, hemithioindigo, 14 indigos, 15 heterodiazocines, 16 arylhydrazones, 17 azo-BF 2 derivatives, 18 imidazolyl-based radicals 19 and coumarin-dienes 20 have all demonstrated excellent visible-light switching properties, including examples of biphotochromic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the commercial applications such as in sunglass lenses, photochromic molecules allow light to be used to reversibly control molecular properties for the development of light-controllable molecular tools, 3 controlling energy transfer 4 or self-assembly, 5 acting as receptors, 6 powering molecular machines, 7 for drug delivery, 8 or modifying material properties. 9 Dithienylethene, 10 spiropyran, 5 , 11 oxazine 12 and azobenzene 9a , 13 are classic photochromic molecules and examples exist in all of these groups where visible light can be used to drive the photoisomerisation. More recently, hemithioindigo, 14 indigos, 15 heterodiazocines, 16 arylhydrazones, 17 azo-BF 2 derivatives, 18 imidazolyl-based radicals 19 and coumarin-dienes 20 have all demonstrated excellent visible-light switching properties, including examples of biphotochromic systems.…”
Section: Introductionmentioning
confidence: 99%
“…S2): degradation could play a role in this as well as other mechanisms such as crystallization and dye reorientation. Degradation mechanisms of this class of dyes have been extensively studied in the literature: [38][39][40][41][42] the dye host has a significant impact on stability. [43] Overall improvements in the dye lifetime will be necessary before it may be widely used in applications but extended switching capabilities have already been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Fixed the quantum yield of the transformations (ϕCOUV,ϕOCUV), the time required to reach a stationary situation decreases while increasing the ratio εOUV/εCUV. It has been also demonstrated that this ratio affects the fatigue resistance of the diarylethenes [51].…”
Section: Diarylethenes: Properties Modulationmentioning
confidence: 99%